Sharia Economic Bankruptcy Law (al-Taflis) and the Dualism of Court Competency in Indonesia - Prihasmoro, Adi; Sopyan, Yayan; Abdullah, Raihanah; Sufiarina, Sufiarina (JURIS (Jurnal Ilmiah Syariah), 2024)
Since Religious Court Law was amended by Law No. 3 of 2006, every sharia economic case is stipulated as the competency of the Religious Court. Conversely, Bankruptcy Law No. 37 of 2004 has never been synchronized with the amended Religious Courts Law. Therefore, the competent court does not handle sharia economic bankruptcy (al-taflis) cases. This study aims to ensure that al-taflis can be examined based on sharia economic principles by the most appropriate judicial forum. It is normative legal research using primary and secondary legal materials such as court decisions, statutory, books, journals, reports, and internet sources, then analyzing and synchronizing to get an ideal formula regarding how al-taflis cases are settled in court. The result shows that al-taflis is appropriately stipulated as the absolute competence of Religious Courts. Case studies of al-taflis court decisions settled by the Commercial Court so far, also indicate that sharia principles are not sufficiently considered in the decisions, even ignored. Therefore, it is urgent to make synchronization efforts by amending the Bankruptcy Law until it can accommodate the settlement of al-taflis case through Religious Courts. Otherwise, it will be only a utopian sharia economic bankruptcy law